Penerapan Metode Ceramah Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di SMP Hidayutullah Medan - Putri, Yolan Dahri; Setiawan, Muhammad Raihan; Yusmeini, Dinda (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
This research aims to explain the application of the lecture method in improving student learning outcomes in pie subjects at SMP Hidayatullah Medan. The research method used is qualitative, with data collection techniques through observation and questionnaires. Based on the research that has been carried out, researchers can draw the conclusion that: the method applied in the pie learning process by teachers is the lecture method. The learning outcomes of students in classes that apply the lecture method in class have increased from a cognitive perspective, and from an affective perspective, students can receive learning well.